ОЦЕНКА РЕСУРСА ВЫСОКОВОЛЬТНЫХ КОНДЕНСАТОРОВ ПО РЕЗУЛЬТАТАМ ИСПЫТАНИЙ НА ПЕРЕМЕННОМ НАПРЯЖЕНИИ - Бутко, С.М.; Рудаков, В.В.; Сергеева, Е.Е.; Рудаков, С.В. (Інститут електродинаміки НАН України, Київ, 2012)
The method of calculation of life time of high-voltage impuls capacitors with a film dielectric on results the tests of sections of capacitors on AC voltage is presented. Correcting dependence of re-calculation of life time is offered. References 3, figure 1.